Kompresi File Aplikasi Hadist Dengan Menggunakan Algoritma Punctured Elias Code - Dewianingsih Yuni (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2020)
The size of the application file is sometimes relatively large, where the better the quality of the application file, the larger the file size needed to store the application file. With a very large application file size, during the transfer process, the transfer process may fail because the media storage space exceeds the limit. The solution to this problem is that the application files can be compressed in order to speed up transferring and storing application files. Compression of application files can be done by reducing the size of the application files by reducing the bits in the application files, but not eliminating or creating corrupted application files. By compressing, large data will be reduced in size so as to save storage space. In this study, the algorithm used is Punctured Elias Code, by using this algorithm, the compression results of the values have different results for each value, and the compression results will make sending and moving application files easier.Keywords: Compression, Files, Hadith Applications, Algortima Punctured Elias Code.